Emerging Technologies for Gut Microbiome Research - Arnold, Jason W.; Roach, Jeffrey; Azcarate-Peril, M. Andrea (Trends in microbiology (Regular ed.), 2016)
Understanding the importance of the gut microbiome on modulation of host health has become a subject of great interest for researchers across disciplines. As an intrinsically multidisciplinary field, microbiome research has been able to reap the benefits of technological advancements in systems and synthetic biology, biomaterials engineering, and traditional microbiology. Gut microbiome research has been revolutionized by high-throughput sequencing technology, permitting compositional and functional analyses that were previously an unrealistic undertaking. Emerging technologies, including engineered organoids derived from human stem cells, high-throughput culturing, and microfluidics assays allowing for the introduction of novel approaches, will improve the efficiency and quality of microbiome research. Here, we discuss emerging technologies and their potential impact on gut microbiome studies. Compositional and functional analyses of the gut microbiome by next-generation sequencing methods have completely transformed research approaches to determine microbial species and their role in human health and disease. New culturing technologies facilitate mechanistic studies of difficult-to-culture gut microbes. A number of previously uncultivable microbes are now cultivable as a result of these advancements, providing insight into community dynamics and network interactions. Stem cell technologies and tissue engineering allow for construction of organoids capable of facilitating cost-effective, high-throughput microbiome studies. Modulation of the gut microbiota is emerging as an effective method to delineate composition and function of microbial communities, providing new methods to prevent and treat disease.